The actin associated protein palladin is important for the early smooth muscle cell differentiation. - Li Jin; Qiong Gan; Bartosz J Zieba; Silvia M Goicoechea; Gary K Owens; Carol A Otey; Avril V Somlyo (PLoS ONE, 2010)
Palladin, an actin associated protein, plays a significant role in regulating cell adhesion and cell motility. Palladin is important for development, as knockdown in mice is embryonic lethal, yet its role in the development of the vasculature is unknown. We have shown that palladin is essential for the expression of smooth muscle cells (SMC) marker genes and force development in response to agonist stimulation in palladin deficient SMCs. The goal of the study was to determine the molecular mechanisms underlying palladin's ability to regulate the expression of SMC marker genes. Results showed that palladin expression was rapidly induced in an A404 cell line upon retinoic acid (RA) induced differentiation. Suppression of palladin expression with siRNAs inhibited the expression of RA induced SMC differentiation genes, SM α-actin (SMA) and SM22, whereas over-expression of palladin induced SMC gene expression. Chromatin immunoprecipitation assays provided evidence that palladin bound to SMC genes, whereas co-immunoprecipitation assays also showed binding of palladin to myocardin related transcription factors (MRTFs). Endogenous palladin was imaged in the nucleus, increased with leptomycin treatment and the carboxyl-termini of palladin co-localized with MRTFs in the nucleus. Results support a model wherein palladin contributes to SMC differentiation through regulation of CArG-SRF-MRTF dependent transcription of SMC marker genes and as previously published, also through actin dynamics. Finally, in E11.5 palladin null mouse embryos, the expression of SMA and SM22 mRNA and protein is decreased in the vessel wall. Taken together, our findings suggest that palladin plays a key role in the differentiation of SMCs in the developing vasculature.